Western Balkans Regional R&D Strategy for Innovation - World Bank (Washington, DC, 2014)
A coordinated effort to develop a regional research and development (R and D) strategy for innovation was launched by the Joint Statement of Sarajevo, signed on April 24, 2009, by the ministers from the Western Balkans (WB) responsible for science and research; the European Union (EU) commissioner for science and research; and the Czech Republic Presidency of the Council of the European Union, under the auspices of the regional cooperation council secretary general. In June 2011, the World Bank signed an agreement with the European Commission (EC) to provide technical assistance for the development of the WB regional R and D strategy for innovation technical assistance (RIS-TA). The strategy aims to strengthen the region's research capacity, enhance intraregional cooperation, promote collaboration with business sectors, explore possibilities for financing R and D from EU funding schemes and other external sources, and help integrate the region into the European research area (ERA) and innovation union. This report is organized as follows: section one gives introduction; section two gives strategic context; section three describes reform program; section four presents action plan for regional cooperation; and section five presents proposed programs.